2008
DOI: 10.1177/1094428108319905
|View full text |Cite
|
Sign up to set email alerts
|

The Case Study as Disciplinary Convention

Abstract: This article explores case study practices within a specific management discipline, that of international business. The authors contrast the case study debate in the general methodological literature to how this method is practiced within this particular scientific community. They review 135 case study—based articles published in four international business journals from 1995 to 2005 and 22 from 1975 to 1994, finding the disciplinary convention in these journals to be exploratory, interview-based multiple case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 417 publications
(95 citation statements)
references
References 73 publications
(85 reference statements)
1
84
0
10
Order By: Relevance
“…Moreover, one review found that case studies were the most popular qualitative research strategy primarily due to its potential to generate novel and groundbreaking theoretical insights (Piekkari et al, 2009). …”
Section: Ep 2017 (64) 2 (483-496)mentioning
confidence: 99%
“…Moreover, one review found that case studies were the most popular qualitative research strategy primarily due to its potential to generate novel and groundbreaking theoretical insights (Piekkari et al, 2009). …”
Section: Ep 2017 (64) 2 (483-496)mentioning
confidence: 99%
“…Los estudios de casos es la estrategia preferida cuando se pretende responder a preguntas del tipo "cómo" y "por qué", cuando el investigador tiene poco control sobre los acontecimientos y cuando el centro de atención es un fenómeno contemporáneo dentro de un contexto de la vida real (Yin, 2003). El estudio de casos examina, a través del uso de una variedad de fuentes de datos, un fenómeno en su contexto natural, con el propósito de confrontar la teoría con el mundo empírico (Piekkari, Welch y Paavilainen, 2008). La confrontación puede hacerse identificando variables para luego testarlas teóricamente o bien buscando una explicación holística de cómo los procesos y las causas encajan juntos en cada caso individual (Ragin, 1992).…”
Section: Justificación De La Metodología Empleada En La Investigaciónunclassified
“…Los estudios de casos se pueden utilizar de dos formas, positivista, que es lo que mayormente domina en la literatura (Piekkari, Welch y Paavilainen, 2008) y, por otro lado, para contrastar la no existencia de un fenómeno determinado. El positivismo trata de explicar y predecir las actividades sociales a través de la identificación de relaciones y reglas de los fenómenos investigados (Bryman y Bell, 2003).…”
Section: Justificación De La Metodología Empleada En La Investigaciónunclassified
See 2 more Smart Citations